2015
DOI: 10.1016/j.jacc.2015.05.030
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of and Adherence to Guideline-Recommended Lipid-Lowering Therapy After Acute Coronary Syndrome

Abstract: In addition to aggressive lifestyle and nonlipid risk factor modification, statin therapy improves cardiovascular disease outcomes following acute coronary syndromes. Despite established benefits of treatment, contemporary registries reveal substantial underutilization of and nonadherence to statin therapy for secondary prevention. In randomized controlled trials investigating statin therapy, including moderate-intensity statin plus ezetimibe therapy, rates of nonadherence are reported in up to 40% of subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(68 citation statements)
references
References 61 publications
3
63
1
1
Order By: Relevance
“…Good adherence to guideline-recommended statin use has been proven to be associated with an improved outcome. (11)(12)(13) In a systematic review of statin discontinuation in high risk patients, Sandoval et al reported that poor adherence and withdrawal of statin therapy led to increased cardiovascular events, cerebrovascular events and mortality both in primary and secondary prevention, as well as in the pre-operative setting. Specifically, statin discontinuation was associated with a 67% increased risk of an acute myocardial infarction, suggesting a potential rebound effect after statin withdrawal.…”
Section: Where Do We Stand: Poor Adherence To Statin Usementioning
confidence: 99%
“…Good adherence to guideline-recommended statin use has been proven to be associated with an improved outcome. (11)(12)(13) In a systematic review of statin discontinuation in high risk patients, Sandoval et al reported that poor adherence and withdrawal of statin therapy led to increased cardiovascular events, cerebrovascular events and mortality both in primary and secondary prevention, as well as in the pre-operative setting. Specifically, statin discontinuation was associated with a 67% increased risk of an acute myocardial infarction, suggesting a potential rebound effect after statin withdrawal.…”
Section: Where Do We Stand: Poor Adherence To Statin Usementioning
confidence: 99%
“…(11) Poor adherence to statins has been associated with increased risk for recurrent cardiovascular events and mortality, increased healthcare costs, and preventable readmissions. (1215) Previous studies have documented substantial nonadherence to statins after hospitalization for AMI,(1618) but few data have been published on changes in adherence to statins from before to after an AMI hospitalization. (19) Determining the impact of an AMI hospitalization on adherence to statins after discharge can guide clinical expectations of statin adherence and can inform the design of interventions to improve adherence.…”
Section: Introductionmentioning
confidence: 99%
“…In reality, many patients are either not at maximally tolerated doses or are non-adherent with their current therapies. (57) Optimizing therapies may reduce the size of the population who could potentially benefit from PCSK9 inhibitors, and our estimates may be an upper bound of the value of PCSK9 inhibitors in these populations. Also, other interventions besides PCSK9 inhibitors could be considered as comparators for cholesterol management, such as more aggressive lifestyle changes relevant to risk factors.…”
Section: Discussionmentioning
confidence: 95%